Time-varying risk and return in the bond market: a test of a new equilibrium pricing model - Campbell, C. J. (Review of Financial Studies, 1999)
This article uses bond market data to empirically test the asset pricing model of Kazemi (1992). According to this model the rate of return on a long-term, pure-discount, default-free bond will be perfectly correlated with changes in the marginal utility of the representative investor. The covariability between financial asset returns and returns on such a bond can therefore serve as a measure of the riskiness of assets. The aim of this study is to determine whether the model can explain cross-sectional differences in the monthly returns of bonds with different maturity dates. We estimate and test the restrictions imposed by the model on returns of default-free bonds, while allowing the conditional distribution of bond returns to be time varying. The model is rejected during the full sample period (1973–1995) and the subperiod (1973–1980) when the Federal Reserve's focus is on interest rates, while the model is not rejected during the subperiod (1981–1995) when the Federal Reserve's focus is on money supply.